69 Association of TERC Related Genetic Variation and Telomerase Activity with Ventricular Arrhythmias in Ischaemic Cardiomtyopathy. (6th June 2015) - Sawhney, Vinit; Brouilette, Scott; Campbell, Niall; Coppen, Steven; Baker, Victoria; Hunter, Ross; Dhinoja, Mehul; Earley, Mark; Sporton, Simon; Suzuki, Ken; Schilling, Richard
Abstract : Introduction: Implantable cardioverter defibrillators (ICD) reduce mortality in ischaemic cardiomyopathy patients at a high risk of ventricular arrhythmias (VA), which are the commonest cause of sudden death. However, ICDs are associated with morbidity and mortality. Importantly 67% of patients never receive an appropriate shock after ICD implantation under current guidelines, suggesting a need for better risk stratification. Telomere and telomerase activity (TA) in leukocytes have recently been shown to correlate with biological ageing and pathogenesis of cardiovascular diseases. Telomerase maintains telomere length and is composed of reverse transcriptase TERT and RNA template TERC. Evidence suggests that genetic variation in key genes has a key impact on TA. Association of SNP12696304 on chromosome 3q26 (at a locus that includes TERC) with telomere length has been shown. We investigated the association between genetic variation in SNP12696304 and leukocyte TA with incidence of VA in ischaemic cardiomyopathy patients. Methods: 90 ischaemic cardiomyopathy Caucasian patients with primary prevention ICDs were recruited. Genomic DNA was isolated from venous blood samples. TA was measured by the telomere repeat amplification protocol and genotyping done using Taqman SNP assay. Continuous data were compared by unpaired T-test and categorical data by Chi-square test. Logistic regression was used to determine correlation of genotype and TA with VA. Results: There was no significant difference in baseline demographics between patients with VA(Cases) and no-VA(Controls) as shown in Table 1 . The TA was significantly higher in the cases and correlated with incidence of VA (p-value 0.02). No significant correlation between the genotype and VA was identified (C/C OR 1; C/G OR 0.54, CI 0.21 – 1.417, p-value 0.343; G/G OR 0.80, CI 0.198 – 3.236, p-value 0.907). There was a significant correlation between risk of VA and TA increase in C/C genotype (OR7.5, CI1–56.6, p-value 0.04). This correlation was not significant in the G/G or C/G genotype as shown in Figure 1 . Conclusion: There is a significant correlation between TA and VA in ischaemic cardiomyopathy patients. Moreover, homozygosity for C allele of SNP 12696304 (encoding TERC) significantly effects telomerase expression. Thus, increased TA predisposes individuals with C/C genotype to a higher incidence of VA. TA in this genotype can be developed as a biomarker to predict VA and guide ICD prescription in ischaemic cardiomyopathy.